Passive façade solutions: tromble wall thermal performance and glazing daylighting performance for Guimarães - Portugal - Sacht, Helenice Maria (2013)
Recently façade systems have integrated passive solutions to reduce the energy consumption in buildings and improve their occupants’ comfort. This paper reports the results of the thermal performance of Trombe walls and daylighting of glazing modules of a façade system in Portugal. Trombe walls are massive walls separated from the outdoors by glazing and an air space, which absorbs the solar energy and releases it selectively to the inside of the building at night. Computational simulations were carried out with the Design Builder, Ecotect and Desktop Radiance programs. The use of Trombe walls and double self-cleaning glass in the façade system led to a decrease in the heating energy needs.